The Neuraminidase Stalk Deletion Serves as Major Virulence Determinant of H5N1 Highly Pathogenic Avian Influenza Viruses in Chicken - Stech, Olga (Sci Rep, 2015)
Highly pathogenic avian influenza viruses (HPAIV) cause devastating losses in gallinaceous poultry world-wide and raised concerns of a novel pandemic. HPAIV develop from low-pathogenic precursors by acquisition of a polybasic HA cleavage site (HACS), the prime virulence determinant. Beside that HACS, other adaptive changes accumulate in those precursors prior to transformation into an HPAIV. Here, we aimed to unravel such virulence determinants in addition to the HA gene. Stepwise reduction of HPAIV genes revealed that the HPAIV HA and NA form a minimum set of virulence determinants, sufficient for a lethal phenotype in chicken. Abolishing the NA stalk deletion considerably reduced lethality and prevented transmission. Conversely, the analogous stalk deletion reconstructed in the NA of an LPAIV reassortant carrying only the HPAIV HA resulted in 100% lethality both after primary and contact infection. Remarkably, the unmodified LPAIV NA with its long stalk, when exclusively introduced into the H5N1 HPAIV, still enabled high virulence and efficient transmission. Therefore, irrespective of an NA stalk deletion, minor virulence determinants in addition to the essential polybasic HACS contribute to high virulence, whereas the NA stalk deletion alone may serve as major virulence determinant.